Potential Therapeutic Options for COVID-19: Current Status, Challenges, and Future Perspectives - Sarkar, Chandan; Mondal, Milon; Torequl Islam, Muhammad; Martorell, Miquel; Docea, Anca Oana; Maroyi, Alfred; Sharifi-Rad, Javad; Calina, Daniela (Frontiers in Pharmacology, 2020)
The COVID-19 pandemic represents an unprecedented challenge for the researchers to offer safe, tolerable, and effective treatment strategies for its causative agent known as SARS-CoV-2. With the rapid evolution of the pandemic, even the off-label use of existing drugs has been restricted by limited availability. Several old antiviral, antimalarial and biological drugs are being reconsidered as possible therapies. The effectiveness of the controversial treatment options for COVID-19 such as non-steroidal anti-inflammatory drugs, angiotensin 2 conversion enzyme inhibitors and selective angiotensin receptor blockers was also discussed. A systemic search in the PubMed, Science Direct, LitCovid, Chinese Clinical Trial Registry, and ClinicalTrials.gov databases was conducted using the keywords ‘coronavirus drug therapy’, passive immunotherapy for COVID-19’, ‘convalescent plasma therapy’, ‘drugs for COVID-19 treatment’, ‘SARS-CoV-2’, ‘COVID-19’, ‘2019-nCoV’, ‘coronavirus immunology’, ‘microbiology’, ‘virology’, and individual drug names. Systematic reviews, case presentations and very recent clinical guidelines were included. This narrative review summarizes the available information on possible therapies for COVID-19, providing recent data to health professionals.